Соціальні фактори прихильності студентів до моди - Байдак, Тетяна Михайлівна; Болотова, Вікторія Олександрівна; Ляшенко, Наталія Олександрівна (Класичний приватний університет, 2019)
У статті уточнено поняття "мода", визначено умови виникнення моди, особливості її функціонування в студентському середовищі. Наведено дані конкретного соціологічного дослідження, за результатами якого виявлено специфіку впливу моди на поведінку сучасної студентської молоді та визначено чинники прихильності студентів до модних тенденцій. Отримані дані можуть бути корисними для установ різної форми власності щодо використання моди як засобу впливу на поведінку студентської молоді.

Fashion is a specific and dynamic form of standardized mass behavior, which occurs as spontaneous behavior under the influence of the dominant mood in society and rapidly changing preferences. Fashion on the one hand helps young people to demonstrate their belonging to their social group, on the other hand, to separate themselves from other groups, to emphasize their individuality. When behavior, which is considered fashionable among young people, becomes an integral part of the personality, its internal need, the fashion becomes a value. Fashion performs a number of important functions, through which young people feel their unity with the group and society in general: it regulates behavior, helps to identify the person itself, promotes communication, helps to show individuality and provides socialization. The article presents the data of a specific sociological study, the results of which revealed the influence of fashion on the behavior of contemporary student youth and determine the factors of student commitment to fashion trends. It is found that about a half of students believe that a fashionable person should follow the new trends, be well groomed, tidy with a good style. At the same time, they have such key characteristics as stylish appearance, confidence, creativity and intelligence. The survey showed that there is a difference in the perceptions of a fashionable man in men and women. Men believe that a fashion person is the first and foremost a follower of trend change and stands out from the majority, while women believe that a fashion person is, above all, a well-groomed person with a neat haircut and a sense of style. The most important motives influencing the students’ desire to follow the fashion, there was a desire to be like others, attract attention of the people of the opposite gender. It is revealed that the main fashion directions for students are the appearance, accessories, profession and level of education. The motivation of respondents of all ages to try to be fashionable has certain differences. Younger respondents follow the fashion because they want to be liked by others, increase their self-confidence and attract attention. Older students want to be fashionable in order not to be different from others. The fashion may lead to quite significant changes in the behavior of the young person who has a positive influence, in the form of acquiring useful habits, and negative, in the form of bad habits. About half of the respondents did not buy any useful and bad habits, but the other half, was subjected to "fashionable" influence and have "fashionable" habits. The obtained data of the conducted research can be useful for various types of commercial, state, and public organizations regarding the use of fashion as a means of influencing the behavior of student youth.
Social Factors of Student Commitment to Fashion
Keywords: студентська молодь; мотивація; модні тенденції; fashion behavior; students; motives of fashion behavior; factors of adherence to fashion